Bilateral Tuberculous Otitis Media: A Rare Presentation - Vijayendra, Honnurappa; Mahajan, Nilesh; Vijayendra, Vinay (Annals of Otology and Neurotology, 2018)
Introduction Tuberculosis is one of the most common infectious diseases in India. Tuberculosis of the middle ear is rare, usually seen in association with pulmonary tuberculosis or in patients with history of pulmonary tuberculosis. It is an uncommon and frequently misdiagnosed form of tuberculosis. In our experience, we have seen 50% of cases of tuberculous otitis media without pulmonary tuberculosis. These cases presented with rapid deterioration of hearing with more sensorineural component in hearing loss.Case Report This is a case report of 34-year-old woman presented to us with worsening of hearing over short duration of 3 months. She developed right profound hearing loss and left moderately severe mixed hearing loss, which deteriorated within duration of 2 weeks. Very few cases have been reported in literature affecting both the ears. In our experience, we have seen seven such cases with bilateral ear involvement.Conclusion Tuberculosis of the middle ear is a rare condition. For complete cure, medical therapy should be given at least for 9 months including 2 months 4 tablets (AKT4) and 7 months 3 tablets (AKT3) regimes, according to the INDEX-TB guidelines provided by government of India for extrapulmonary tuberculosis. Surgical treatment should be always added as emergency to prevent progression of sensorineural hearing loss and in cases of complications such as facial palsy.
Keywords: tuberculous otitis media; AKT4; AKT3; INDEX-TB guidelines